Answer:
We have a + b as;
2 + 3 = 5
Step-by-step explanation:
Here, we want go get the value of a and b
from the second equation, we can get an expression for b
We have this as;
7a - b = 11
Thus,
b = 7a - 11
Now, from here, we can substitute the value of b into the first equation
We have this as;
5a + 4(7a - 11) = 22
5a + 28a -44 = 22
33a = 22 + 44
33a = 66
a = 66/33
a = 2
Recall;
b = 7a - 11
substituting the value of a from above;
b = 7(2) - 11
b = 14 - 11
b = 3
Let ‘s’ be the son’s age 12 years ago.
Let ‘f’ be the father’s current age.
4 years ago, the son was:
s-4
So, his father is currently:
3(s-4)
=
3s-12
Therefore:
f = 3s-12
In twelve years, the son will be:
s+12
And the father will be:
f+12
This can also be written as:
3s-12+12 as the fathers younger age would be f = 3s+12
=
3s
So, we know that s+12 is half the fathers current age, meaning the father is currently 2(s+12) which is equivalent to 2s+24. Also, we know that the father is currently 3 times the sons age 12 years ago, so 3s (proven by the calculations we made above). Therefore, 2s+24=3s which means 24=s. We can then substitute this, and we will receive 24+12 = 36
Son’s current age: 36
We then substitute the son’s age 12 years ago into 2s+24 to give us the father’s age.
2(24)+24 = 72
Father’s current age: 72
Find the quotient: (25c^4 + 20c^3) ÷ 5c5c^3+4c^2.
Answer:
-3
2
5
Step-by-step explanation:
Answer:
I may not be correct, depending on what you were taught, but it would be...
17/30
Step-by-step explanation:
(2/5×6/6)+(1/6×5/5)
12/30 + 5/30
17/30
keep in mind you don't add the denominators at all ( the numbers at the bottom half of the fraction)